The effects of curcumin on musculoskeletal pain: a systematic review protocol. (February 2015) - Gaffey, Andrew; Campbell, Jared; Porritt, Kylie; Slater, Helen
Abstract : Review question/objective : The objective of this review is to identify the effectiveness of curcumin on musculoskeletal pain. More specifically, the objectives are to identify the effectiveness of the use of turmeric, turmeric extract, and/or curcuminoids to modulate musculoskeletal pain. Background : Curcuma longa (turmeric) from the Ginger family (Zingiberacea) is native to Southeast India, and has been used for centuries in cooking and in medicine.1–4 The rhizome (root) of the plant is the portion most commonly used in cooking and when cut has a bright orange‐yellow appearance.5 It is usually prepared by grating the fresh root, or alternatively, drying the root then grating to a bright orange‐yellow powder.6 The fresh‐grated rhizome or the dried powder is used in cooking as a base ingredient in curries and soups and as a food colouring.7 Historically, turmeric has been used medicinally to assist in the control of inflammation, 8 and pain.9, 10 The methods of delivery of the bioactive substances for medicinal use include being eaten, or being applied to the skin, gums11 or wounds, 12 as a paste, 13, 14 poultice, or gel.15 Turmeric contains at least three naturally‐occurring polyphenols termed curcuminoids: curcumin; demethoxycurcumin; and bisdemethoxycurcumin.3 Various studies describe the total curcuminoids by percentage in the turmeric root as falling between 3% and 6% of dry weight.16, 17 Curcumin is the most prevalent curcuminoid found in turmeric, 8 making up around 77% of the total curcuminoids in the plant. Demethoxycurcumin makes up about 17% of the total curcuminoids and bisdemethoxycurcumin about 5%.18 Polyphenols are naturally occurring compounds found in fruits, vegetables and grains.19, 20 There is evidence to suggest that polyphenols are produced by plants for protection from damage by ultraviolet radiation and to deter predators.21, 22 Foods regularly consumed by humans which have been shown to be high in polyphenols include red wine, green and black tea, 19 cocoa, 20 fruits such as grapes, cherries and apples22, some spices22 and grains. There are four groups of polyphenols which include: flavonoids such as quercetin; phenolic acids; stilbenes such as resveratrol found in grapes; and lignans, several of which are phytoestrogens.19 Polyphenols have been shown to have an antioxidant effect in tissues, and there appears to be an inverse relationship, found by epidemiological studies. between the consumption of a polyphenol‐rich diet and the occurrence of chronic disease such as cardiovascular disease in humans.23 McKeown et al.20 determined that polyphenol‐rich foods can effect a significant improvement in endothelium‐dependent vasodilation following an 8‐week intervention in hypertensive participants. There is little discussion in the literature directly investigating the effect of polyphenols in modulating pain in humans. A small study (14 subjects) investigating the effect of a polyphenol‐rich blend of fruit juices and pulp on pain and range of motion with results indicating improvement in pain and ROM correlated best with an improvement seen in serum antioxidant status.24 Yin et al.25 suggest that resveratrol facilitates pain attenuation in a rat model of neuropathic pain, and in an unrelated study, resveratrol was able to reduce levels of proinflammatory cytokines in vitro and showed pain‐reduction potential in a rat model of radiculopathy.26 The authors concluded that the reduction of pain in vivo may have been due to resveratrol's effect on proinflammatory cytokines.26 Additionally, various researchers have recognized the anti‐inflammatory and antinociceptive potential of mangiferin and suggest that it could be used to treat neuropathic pain.27, 28 The three polyphenols found in turmeric are postulated to have various bioactive effects, and there is evidence for their effectiveness in the treatment of joint inflammation, 29 intervertebral disc inflammation, 30 depression, 31 burn pain, 32 the reduction of serum triglycerides, 33 diabetic neuropathic pain, 34–36 and enhancing wound‐healing.32, 37 Active metabolites of curcumin are produced after oral doses of curcumin.38, 39 These include tetrahydracurcumin and hexahydrocurcumin. There is some debate in the literature concerning whether one or all of the curcuminoids, or a specific metabolite of one or all of them, may be responsible for the bioactive effects seen with the use of turmeric and curcuminoids. The bioavailability of curcumin can be enhanced in some ways including heating, and combining with adjuvants.40, 41 Adjuvants are believed to be important as they can block the metabolism of curcumin, thereby increasing the bioavailability.42–44 Piperine preparations inhibit glucuronidation, 17 and have been shown to increase bioavailability by up to 20‐fold.17 Nanoparticle preparations of curcumin, where the particle size has been maintained below 100nm and held in a suspension or gel, 45 have been found to increase bioavailability nine‐fold compared with curcumin‐piperine combinations, 40 and the complexation of curcumin into phytosomes has been shown to improve bioavailability of curcumin via increased absorption of the polyphenol.46, 47 Consequently, commercial preparations of curcumin are often presented as being "bio‐optimized' ‐ due to having been combined with a surfactant such as polysorbate.48, 49 Additionally, there is evidence that suggests that the non‐curcumininoid portion of turmeric increases or potentiates the effects of curcumin.40, 50, 51 Integral to the bioactive effects discussed above is the antioxidant effect of curcumin.37, 52–54 Antioxidants work to remove free radical intermediates, and inhibit other oxidation reactions by being oxidized themselves.21 A bovine study shows curcumin to have antioxidant activity similar to vitamin C, and considerably higher antioxidant activity than vitamin E.52, 53 Pain is defined as an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage by the International Association for the Study of Pain (IASP) Task Force on Taxonomy 1994.55, 56 The human experience of pain is multidimensional and comprises sensory, affective, and cognitive dimensions.57 Pain is always subjective and as such is difficult to quantify. Actual tissue damage results in a myriad of physical and chemical effects in the body. Amongst these effects, tissue injury causes nerve terminals called nociceptors to depolarize, resulting in sensory impulses reaching the spinal cord. At the site of tissue injury various neuropeptides are released which sensitize the nociceptor and increase its rate of firing.58 Inflammatory mediators such as bradykinin, prostaglandins and pro‐inflammatory cytokines released in the area additionally augment the transmission of nociceptive impulses along sensory afferent fibers.59 Recent studies demonstrate that curcumin can act locally at the site of a noxious stimulus to reduce nociception.36, 60, 61 Nociceptive information impulses travel along the sensory afferent fibers from the periphery to the dorsal horn of the spinal cord where they synapse on secondary neurons and interneurons. From the spinal level, impulses are propagated upwards to supra‐spinal centers through several potential pathways and relays.58, 62, 63 The IASP Taskforce on Taxonomy 1994‐2011 specifies that pain is not nociception as nociception is the process of encoding noxious stimuli in the nervous system. Pain can exist with or without nociceptive input and nociception can exist without pain.58, 64 Knowing that pain is a complex sensory experience accompanied by affective, emotive and cognitive aspects is of fundamental importance in the understanding of pain perception.63 Pain is usually produced by the stimulation of specific nociceptors but may also result from injury to sensory fibers, or from damage to the Central Nervous System (CNS) itself.62 Pain can also be experienced in the absence of tissue damage.64 At the local tissue damage area, various naturally‐occurring polyphenols, including curcumin, 19, 65 resveratrol, 19 and mangiferin66 have been shown to modulate the production of inflammatory cytokines. Evidence in tumour studies demonstrates that the anti‐inflammatory effect of curcumin is likely to occur through markedly inhibiting the mRNA and protein expression of cyclooxygenase‐2 (COX‐2), 67 and by inhibiting lipogenase (LOX) and inducible nitric oxide synthase (iNOS).53, 68 Additionally, murine studies have demonstrated a reduction of inflammatory cytokine expression in adipose tissue with the administration of nutritional doses of Curcumin and piperine.44 Chronic pain differs in definition from acute pain, with chronic pain being defined as pain that has lasted longer than three months. Some chronic pain states may involve significantly less local inflammatory markers than acute pain states.69, 70 but could still be assisted by the ingestion of curcumin.69 Musculoskeletal pain is a clinical description of pain arising from musculoskeletal sources. Musculoskeletal sources are bone, joint and muscular tissues.71 Examples of pain from these tissues would include joint pain from trauma such as sprains and strains and joint degeneration, as well as pain from inflammatory conditions such as rheumatoid arthritis (RA). Prevalence of musculoskeletal pain in the general population is high, as noted in the Health Interview Surveys (HIS) and Health Examination Surveys (HES) which are used to determine frequency. There is poor standardization of assessment across populations and cultures. This hampers comparison of data, but frequency of experiencing some form of musculoskeletal pain in the previous week appears to range between about 14% and 47% of the general population, 72 with most people experiencing musculoskeletal pain reporting pain from a number of sites.73, 74 The focus of this review is to investigate the outcomes of studies examining the effect of turmeric, turmeric extract, or curcuminoids on musculoskeletal pain either by themselves or in conjunction with other substances. Recent studies have shown that use of curcuminoids to treat pain associated with knee osteoarthritis shows greater reductions of pain as compared with a placebo75, 76 and compares in efficacy with the use of ibuprofen.77, 78 Another study shows significant efficacy with the use of turmeric extract in combination with other nutraceuticals (devil's claw and bromelain) to treat acute and chronic osteoarthritis pain.79 A recent pilot study demonstrated that a proprietary lecithin formulation of curcumin had a comparative effect of a standard dose of acetaminophen in the treatment of acute pain.47 A small placebo‐controlled pilot study (20 subjects) showed significant reduction of delayed onset muscle soreness and reduced MRI damage findings in subjects who used a proprietary lecithin formulation of curcumin.80 The turmeric root being relatively easy to grow in temperate and tropical areas and tolerating a variety of soil types, 18 could potentially represent a low‐cost, accessible material for use by people with limited access to pharmaceuticals. Additionally, as turmeric ingestion is tolerated in high doses, 14, 40, 81, 82 with low reported toxicity, 2, 83 and is routinely consumed as a normal part of many people's diets, 6 its potential usefulness is enhanced by not requiring intensive supervision of health professionals to guide its administration. There are indications that curcuminoids are poorly absorbed from the gut, 40, 84–86 are practically water‐insoluble substances, 87, 88 and that once absorbed into the system they undergo rapid metabolism40 and are speedily eliminated from the body.39 In the face of these factors, it is important to note that if turmeric is to be used for musculoskeletal pain, it should only be done with clear evidence of effectiveness. As such, this review aims to evaluate the evidence on the effect of curcumin on musculoskeletal pain in humans. A review of the Cochrane Library, JBI Database of Systematic Reviews and Implementation Reports, CINAHL, and other relevant data bases did not find any current or planned systematic reviews on this topic.